Poland’s polar policy in the face of the Arctic Council 2022 cooperation crisis - Łuszczuk, Michał; Rakowski, Piotr; Szkarłat, Monika (Polish Polar Research, 2023)
Developments in Arctic international relations resulting from Russia's aggression against Ukraine in 2022 stand as the most serious crisis in regional cooperation since the end of the Cold War. This crisis has necessitated a re-evaluation of the regional governance system and an update of the political strategies of Arctic stakeholders. In this article, based on qualitative research methodology, we explore the challenges to regional cooperation in the near and mid-term perspectives, and we discuss how the current situation can contribute to a transformation of Poland's role in the Arctic, particularly in the field of science diplomacy. The study includes a critical analysis of the content of the Polish Polar Policy officially adopted in 2020, as well as its implementation. We conclude that the future of Arctic relations will be based not only on the hindered functioning of the Arctic Council but also on the emergence of new competitive forms of collaboration to be developed by Russia and its partners, distancing themselves from Western states. In such a situation and in the face of the emerging opposition between the two blocs, the role of science diplomacy will substantially increase and gain new dynamics. This, in turn, means that although Poland's Arctic policy in its present framework requires only minor conceptual correction, its implementation should be considerably built up and advanced.